2022
DOI: 10.1126/sciadv.abm5120
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of nonsingular defect enabling rapid control of structural color

Abstract: Stimuli-interactive structural color (SC) of a block copolymer (BCP) photonic crystal (PC) uses reversible alteration of the PC using external fluids and applied forces. The origin of the diffusional pathways of a stimulating fluid into a BCP PC has not been examined. Here, we directly visualize the vertically oriented screw dislocations in a one-dimensional lamellar BCP PC that facilitate the rapid response of visible SC. To reveal the diffusional pathway of the solvent via the dislocations, BCP lamellae are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Understanding the diffusion mechanism of swelling agents into a 1D BCP PC consisting of alternating non-swelling and swelling layers is of great importance. Recent studies have shown that the characteristic screw dislocations in a 1D PC were responsible for the fast infusion of a swelling agent; this allowed the fast SC alteration of a BCP PC [ 51 ]. Further enhancement of SC-switching speed can be made by properly controlling the position and areal density of these screw dislocations.…”
Section: Perspectivementioning
confidence: 99%
“…Understanding the diffusion mechanism of swelling agents into a 1D BCP PC consisting of alternating non-swelling and swelling layers is of great importance. Recent studies have shown that the characteristic screw dislocations in a 1D PC were responsible for the fast infusion of a swelling agent; this allowed the fast SC alteration of a BCP PC [ 51 ]. Further enhancement of SC-switching speed can be made by properly controlling the position and areal density of these screw dislocations.…”
Section: Perspectivementioning
confidence: 99%
“…Meanwhile, the photonic characteristics of the structure corresponding to the colour of APCs indicate that the colour of APCs is caused by interference caused by the scattering of light through the spatial distribution in the submicron-scale cavity. 42,43 The colour of SiO 2 @TiO 2− x APCs can be adjusted by controlling the diameter of the nanospheres. After vacuum heat treatment, SiO 2 @TiO 2− x nanospheres with different particle sizes showed rich colours, such as red, green, and blue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the nature of human visual perception of color, it is generally acceptable to combine chromaticity changes with environmental stimuli to form a simple visual detection method. Photonic crystal (PC) is a highly ordered nanoscale structure that can affect the movement of photons. , It has the property of transforming external stimuli into optical signals and is widely used in various modes of sensing. , When the photonic band gap of the PC locates in the visible range, structural color will be generated; and when the refractive index or thickness of the PC changes, the stimulation signal can be transformed into a color variation and a visual detection effect is produced. …”
Section: Introductionmentioning
confidence: 99%